2013
DOI: 10.1371/journal.pone.0072197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in BCL2 3′-UTR Was Associated with Lung Cancer Risk and Prognosis in Male Chinese Population

Abstract: ObjectivesBcl-2 is a critical apoptosis inhibitor with established carcinogenic potential, and can confer cancer cell resistance to therapeutic treatments by activating anti-apoptotic cellular defense. We hypothesized that genetic variants of BCL2 gene may be associated with lung cancer susceptibility and prognosis.MethodsThree selected tagSNPs of BCL2 (rs2279115, rs1801018, and rs1564483) were genotyped in 1017 paired male Chinese lung cancer cases and controls by TaqMan assay. The associations of these varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…The expression of Bcl-2 may serve as predictive biomarker of response to induction chemotherapy in HNSCC (head and neck squamous cell carcinomas) patients (23). The genetic variation in Bcl-2 3'-uTR was associated with a decreased lung cancer risk and better survival for non-small cell lung cancer in male Chinese (24). Overexpression of Bcl-2 protein predicts chemoresistance in acute myeloid leukemia (25).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Bcl-2 may serve as predictive biomarker of response to induction chemotherapy in HNSCC (head and neck squamous cell carcinomas) patients (23). The genetic variation in Bcl-2 3'-uTR was associated with a decreased lung cancer risk and better survival for non-small cell lung cancer in male Chinese (24). Overexpression of Bcl-2 protein predicts chemoresistance in acute myeloid leukemia (25).…”
Section: Introductionmentioning
confidence: 99%
“…Another study provided the evidence that the rs1564483 A allele, located within the 3′-UTR of BCL2 , was associated with a significantly lower risk for LC in male Chinese patients and with a favorable OS in advanced NSCLC patients 29. This effect was more obvious in smoking patients, in stage IIIA patients, and in patients without surgery undergone to chemotherapy or radiotherapy.…”
Section: Lung Cancermentioning
confidence: 97%
“…This effect was more obvious in smoking patients, in stage IIIA patients, and in patients without surgery undergone to chemotherapy or radiotherapy. The authors speculated that the rs1564483 G-to-A substitution might change the stem-loop structure of 3′-UTR or introduce a miRNA binding site, which may affect BCL2 mRNA stability or its expression levels 29. Several miRNAs, including miR-181b,30 miR-200bc/429,31 and miR-204,32 have been reported to bind to the BCL2 3′-UTR in correspondence with the miRSNP, thereby modulating BCL2 mRNA levels.…”
Section: Lung Cancermentioning
confidence: 99%
“…Zhang et al reported that Bcl-2 -938C>A polymorphism may be relevant to the clinical symptoms of major depressive disorder15. Recently, several studies have reported that Bcl-2 -938C>A promoter polymorphism is associated with susceptibility and prognosis of cancer161718192021222324252627282930313233343536373839.…”
mentioning
confidence: 99%